2010
DOI: 10.1111/j.1398-9995.2010.02340.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory profiles in nasal mucosa of patients with persistent vs intermittent allergic rhinitis

Abstract: The findings from the present study suggest that PER is characterized by a significantly greater eosinophilic and predominantly Th2 cell-mediated nasal inflammatory profile compared to IAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
2
12
1
3
Order By: Relevance
“…These findings are similar to those observed in allergic rhinitis in people, which is characterized by mast cell expansion in the nasal mucosa following natural allergen exposure [40,41,42]. Murine models of allergic rhinosinusitis also exhibit nasal mucosal mast cell inflammation that increases over time following chronic allergen exposure [43].…”
Section: Discussionsupporting
confidence: 72%
“…These findings are similar to those observed in allergic rhinitis in people, which is characterized by mast cell expansion in the nasal mucosa following natural allergen exposure [40,41,42]. Murine models of allergic rhinosinusitis also exhibit nasal mucosal mast cell inflammation that increases over time following chronic allergen exposure [43].…”
Section: Discussionsupporting
confidence: 72%
“…It is possible that symptom frequency and duration, rather than symptom severity, may alter SOCS1 and SOCS3 expression in patients with allergic rhinitis. This suggestion is supported by a study showing that moderate/severe persistent allergic rhinitis is characterized by a significantly greater eosinophilic and predominantly Th2 cell-mediated nasal inflammatory profile compared to intermittent allergic rhinitis [27]. However, our study did not evaluate patients with intermittent allergic rhinitis, and future studies investigating SOCS1 and SOCS3 expression in these patients may be promising.…”
Section: Discussionmentioning
confidence: 39%
“…Several studies have demonstrated that the expression of GATA-3 is increased significantly in patients with AR compared with healthy controls [17,31]. Liu et al [27] showed that the expression of GATA-3 mRNA is increased significantly in persistent AR patients compared with those with intermittent AR. GATA-3 is also increased in patients with AR following natural exposure during the pollen season.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant decrease in the T-bet + /GATA-3 + ratio was determined during the pollen season. Liu et al [27] showed that the expression of T-bet mRNA was not significantly different in persistent AR, intermittent AR or control patients.…”
Section: Discussionmentioning
confidence: 99%